Dose-dependent relationship between intra-procedural hypoxaemia or hypocapnia and postoperative delirium in older patients. (February 2023) - Ahrens, Elena; Tartler, Tim M.; Suleiman, Aiman; Wachtendorf, Luca J.; Ma, Haobo; Chen, Guanqing; Kendale, Samir M.; Kienbaum, Peter; Subramaniam, Balachundhar; Wagner, Soeren; Schaefer, Maximilian S.
Abstract: Background: Previous studies indicated an association between impaired cerebral perfusion and post-procedural neurological disorders. We investigated whether intra-procedural hypoxaemia or hypocapnia are associated with delirium after surgery. Methods: Inpatients ≥60 yr of age undergoing anaesthesia for surgical or interventional procedures between 2009 and 2020 at an academic healthcare network in the USA (Massachusetts) were included in this hospital registry study. The primary exposure was intra-procedural hypoxaemia, defined as peripheral oxygen saturation <90% for >2 cohering min. The co-primary exposure was hypocapnia during general anaesthesia, defined as end-tidal carbon dioxide pressure ≤25 mm Hg for >5 cohering min. The primary outcome was delirium within 7 days after surgery. Results: Of 71 717 included patients, 1702 (2.4%) developed postoperative delirium, and hypoxaemia was detected in 2532 (3.5%). Of 42 894 patients undergoing general anaesthesia, 532 (1.2%) experienced hypocapnia. The occurrence of either hypoxaemia (adjusted odds ratio [ORadj ]=1.71; 95% confidence interval [CI], 1.40–2.07; P <0.001) or hypocapnia (ORadj =1.77; 95% CI, 1.30–2.41; P <0.001) was associated with a higher risk of delirium within 7 days. Both associations were dependent on the magnitude, and increased with event duration (ORadj =1.03; 95% CI, 1.02–1.04; P <0.001 and ORadj =1.01; 95% CI, 1.00–1.01; P =0.005, for each minute increase in the longest continuous episode, respectively). There was no association between occurrence of hypercapnia and postoperative delirium (ORadj =1.24; 95% CI, 0.90–1.71; P =0.181). Conclusions: Intra-procedural hypoxaemia and hypocapnia were dose-dependently associated with a higher risk of postoperative delirium. These findings support maintaining normal gas exchange to avoid postoperative neurological disorders.